Chemical composition and antifungal activity of the essential oil of Varronia schomburgkii (DC.) Borhidi (Cordiaceae) from plants cultivated in French Guiana. Issue 4 (4th July 2017) - Scotto, Camille Inès; Burger, Pauline; Khodjet el Khil, Mehdi; Ginouves, Marine; Prevot, Ghislaine; Blanchet, Denis; Delprete, Piero G.; Fernandez, Xavier
Abstract: This study reports for the first time the chemical composition of the essential oil of Varronia schomburgkii (DC.) Borhidi cultivated in French Guiana. This essential oil was examined by a combination of GC/FID and GC-MS techniques and was further tested for antifungal activity against several Candida strains, as well as for anti-leishmanial activity against the reference strain Leishmania guyanensis . A total of 45 components accounting for 93.61% of the total GC/FID chromatogram were identified. The essential oil is dominated by sesquiterpenes and oxygenated sesquiterpenes among which β-caryophyllene (46.99 ± 0.32%) is the major one. No anti-leishmania activity could be assessed, while a strong antimicrobial activity of this essential oil was evidenced in vitro against a Candida albicans strain by the definition of a MIC value of 250 μg/mL. V. schomburgkii essential oil might hence be considered in the future for the development of natural antifungal agents.